Phrynoderma and acquired acrodermatitis enteropathica in breastfeeding women after bariatric surgery - Monshi, Babak; Stockinger, Theresa; Vigl, Kornelia; Richter, Leo; Weihsengruber, Felix; Rappersberger, Klemens (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
Summary Background and objectives Women who have undergone bariatric surgery are susceptible to nutritional deficiencies in subsequent pregnancies. We highlight the importance of dermatologists in the early recognition of cutaneous signs of malnutrition occurring in this specific clinical setting. Patients and methods We compare clinical characteristics of two young women with dermatological signs of combined post‐gestational nutritional deficiencies following Roux‐en‐Y gastric bypass surgery. Results Patient 1 exhibited follicular papules on the extremities, perianal eczema, perlèche, alopecia, and depigmentation of hair. Patient 2 showed erythematous plaques in genitoanal and acral areas, perlèche, diffuse alopecia, and depigmentation of hair. Based on clinical and histopathological findings, decreased vitamin A (patient 1) and zinc levels (patient 2), we diagnosed phrynoderma and acquired acrodermatitis enteropathica, respectively. Comparison of the two patients revealed that both (i) were lacking follow‐up after gastric bypass surgery, (ii) developed skin lesions as primary symptoms with (iii) mixed clinical manifestations due to combined deficiencies, and (iv) experienced initial symptoms during lactation suggesting a causal relationship. Conclusions Our observations highlight the potentially increased risk of women to develop post‐gestational dermatological manifestations of malnutrition following bariatric surgery. The awareness of dermatologists with respect to this emerging, susceptible patient group may help avert damage to mother and child.